Marine Gas Hydrate Geohazard Assessment on the European Continental Margins: the Impact of Critical Knowledge Gaps - León Buendía, Ricardo F.; Llorente Isidro, Miguel; Giménez-Moreno, Julia (Applied Sciences, 2021)
23 p. - Data used in this paper are available in a public and permanent repository (https://data.mendeley.com/datasets/vbt6hspgpn/draft?preview=1, (accessed on 20 March 2020)) with doi:10.17632/vbt6hspgpn.1. [EN] This paper presents a geohazard assessment along the European continental margins and adjacent areas. This assessment is understood in the framework of the seafloor’s susceptibility to (i.e., likelihood of) being affected by the presence of hydrate deposits and the subsequent hazardous dissociation processes (liquefaction, explosion, collapse, crater-like depressions or submarine landslides). Geological and geophysical evidence and indicators of marine gas hydrates in the theoretical gas hydrate stability zone (GHSZ) were taken into account as the main factors controlling the susceptibility calculation. Svalbald, the Barents Sea, the mid-Norwegian margin-northwest British Islands, the Gulf of Cádiz, the eastern Mediterranean and the Black Sea have the highest susceptibility. Seafloor areas outside the theoretical GHSZ were excluded from this geohazard assessment. The uncertainty analysis of the susceptibility inference shows extensive seafloor areas with no data and a very low density of data that are defined as critical knowledge gaps. This research was funded by the European Union’s Horizon 2020 research and innovation programme under grant agreement No 731166, GARAH project (GeoERA- GeoE.171.002 GE-1), EMODnet Bathymetry—High Resolution Seabed Mapping (EASME/EMFF/2018/007). Peer reviewed